2017
DOI: 10.15406/joentr.2017.09.00277
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Chronic Suppurative Otitis Media: A Prospective Study in a Tertiary Care Hospital

Abstract: Objective: Aim of the study is to find out the microbiological profile and their antibiotic sensitivity patterns in patients with chronic suppurative otitis media in a tertiary care hospital. Materials and methods:A total number of 100 ear swabs were investigated for the present study. Their gram staining, direct microscopy with KOH, culture sensitivity, and biochemical tests were carried out to identify the organisms and to know their sensitivity pattern. All the swabs were collected from patients with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results of the current study were in consistence with John et al, (39), Balan and Viswanatha, (40) reported that common fungal agents causing secondary infection in Chronic suppurative otitis media (CSOM) are Candida spp., Aspergillus spp., Rhizopus spp., and Penicillium spp. Previous literature showed that among the fungal isolates, Aspergillus as well as Candida were the most widespread species responsible for otomycosis globally but other causative isolated fungi species have been belonged to genera Penicillium, Fusarium, Mucoraceae, Scopulariopsis, Alternaria, Malassezia in addition to various dermatophytes (41).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the current study were in consistence with John et al, (39), Balan and Viswanatha, (40) reported that common fungal agents causing secondary infection in Chronic suppurative otitis media (CSOM) are Candida spp., Aspergillus spp., Rhizopus spp., and Penicillium spp. Previous literature showed that among the fungal isolates, Aspergillus as well as Candida were the most widespread species responsible for otomycosis globally but other causative isolated fungi species have been belonged to genera Penicillium, Fusarium, Mucoraceae, Scopulariopsis, Alternaria, Malassezia in addition to various dermatophytes (41).…”
Section: Discussionsupporting
confidence: 90%
“…Chronic suppurative otitis media has a significant impact on hearing loss and can cause complications if not treated appropriately 9 . The use of antibiotics has reduced the incidence of CSOM complications, but the use of antibiotics incorrectly leads to germ resistance 9,10 . Therapy CSOM is a challenge in itself because the disease tends to recur easily, and the germs can quickly turn resistant.…”
Section: Israa Hussein Hamzah Noor Al-huda Ali a H Saeed Alaa N Moham...mentioning
confidence: 99%
“…The patterns of germs and antibiotic sensitivity in CSOM patients differ from one place to another 9,11,12 . Understanding germs' pattern and their antibiotic sensitivity will lead to a rational choice of antibiotics to prevent the emergence of resistance 9,10 . This study aims to report the microbiological profile and antibiotic sensitivity patterns in CSOM patients.…”
Section: Israa Hussein Hamzah Noor Al-huda Ali a H Saeed Alaa N Moham...mentioning
confidence: 99%
“…Two prominent GC bacteria that are often co-isolated from chronic infections are Pseudomonas aeruginosa and Staphylococcus aureus. They have been isolated from chronic infections like chronic wounds ( Gjødsbøl et al., 2006 ), pulmonary cystic fibrosis ( Henson et al., 2019 ), chronic osteomyelitis ( Masters et al., 2022 ), and chronic otitis media ( Viswanatha, 2017 ). The dyad, therefore, is of immense interest to researchers studying chronic polymicrobial infections.…”
Section: Introductionmentioning
confidence: 99%